Invariance in Transverse Momentum of Photons in Double-slit Experiment - Abdul Rahim, Muhammad Amsyar; Kamal, Mohd Hafizudin; Othman, Mohd Amir Radhi (Journal of Science and Technology, 2018)
One of the intriguing mystery in modern physics is the quantum interference phenomena, which the behaviour of photons in double-slit experiment is still ambiguous. Instead of relying on the naive probabilistic point of view, Bohmian mechanics provides the ground base for interpreting quantum system in a deterministic way closely related to classical mechanics such as it constructs the photon trajectory for the double-slit set up. The appearance on the bending in the constructed photon trajectory seem to contravene the notable law of conservation of momentum. Here, we report on conservation of the transverse momentum of photon trajectories based on numerical solution of Bohmian mechanics in double-slit set up for single photon, pair of photons and ensemble of photons until interference pattern is produced. It is shown that the total transverse momentum in the system of Bohmian mechanics is invariance due to the non-local action of quantum potential.